Profile of Pre-Service Physics Teachers’ Scientific Literacy Based on Competence Aspects - Firdaus Firdaus; Wiyanto Wiyanto; Ngurah Made Darma Putra; Wiwi Isnaeni; Sri Jumini; Eli Trisnowati (International Conference on Science, Education, and Technology, 2021)
The rapid development of scientific information impacts students' ability to solve problems in daily life based on each student's ability to manage the information. This study aims to analyze and describe the scientific literacy of pre-service teachers in the physics education study program in the second semester. This research method is a descriptive method with a quantitative approach. The data collection technique is a test using a test sheet instrument containing 11 questions about scientific literacy, which consists of 3 aspects: explaining phenomena scientifically, evaluating and designing scientific investigations, and interpreting data and evidence scientifically. Experts have validated the instruments used. The results showed that the overall scientific literacy competence of students was in a low category. One indicator shows the value in the medium category, while the other indicators show the low category. These results indicate that students' scientific literacy skills need to be improved. These findings can be used as a basis for evaluating the learning process by emphasizing the development of students' scientific literacy skills.